Frontispiece: Protonation‐Induced Chirality Drives Separation by Differential Ion Mobility Spectrometry. Issue 9 (15th February 2022) - Ieritano, Christian; Yves Le Blanc, J. C.; Schneider, Bradley B.; Bissonnette, Justine R.; Haack, Alexander; Hopkins, W. Scott
Abstract : Mass Spectrometry The ionization of N‐protonated Verapamil by electrospray ionization (ESI) is investigated in the Communication (e202116794) by W. Scott Hopkins et al. by using differential mobility spectrometry (DMS). The spectral behaviour is caused by protonation‐induced chirality.